2021
DOI: 10.1094/pdis-07-20-1621-re
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Biological and Molecular Characteristics of Resistance to Fludioxonil in Sclerotinia sclerotiorum From Soybean in China

Abstract: Sclerotinia sclerotiorum is one of the most damaging and economically important necrotrophic plant pathogens, infecting more than 400 plant species globally. Although the phenylpyrrole fungicide fludioxonil has high activity against S. sclerotiorum, recent reports have indicated that there is also a substantial potential for the development of fungicide resistance. However, the current study investigating five fludioxonil-resistant laboratory mutants found a significant fitness cost associated with fludioxonil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…At present, the management of S. sclerotiorum in soybean strongly relies on the use of chemical fungicides, such as carbendazim, fluazinam, prochloraz, and procymidone ( Miorini et al, 2021 ). However, none of them offer complete control and several resistant strains have been reported ( Mao et al, 2020 ; Zhou et al, 2020 ). Apart from the low efficacy of commercial fungicides, the management of S. sclerotiorum is a difficult task due to the pathogen’s wide host range, and its persistent resting structures, called sclerotia.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the management of S. sclerotiorum in soybean strongly relies on the use of chemical fungicides, such as carbendazim, fluazinam, prochloraz, and procymidone ( Miorini et al, 2021 ). However, none of them offer complete control and several resistant strains have been reported ( Mao et al, 2020 ; Zhou et al, 2020 ). Apart from the low efficacy of commercial fungicides, the management of S. sclerotiorum is a difficult task due to the pathogen’s wide host range, and its persistent resting structures, called sclerotia.…”
Section: Introductionmentioning
confidence: 99%
“…10 There are significant adaptation costs associated with the resistance of Sclerotinia sclerotiorum to fipronil resulting in reduced mycelial growth, sclerotia, and pathogenicity of potato dextrose agar. 20 Our previous study identified five different-point mutant resistant strains and their biological characteristics showed a decreasing trend. We sequenced the transcriptomes of these five-point mutant resistant strains to analyze the molecular mechanism of reduced fitness of fludioxonil-resistant B. cinerea strains at the whole-genome level to explore the molecular mechanism underlying the reduced biological fitness of B. cinerea resistant to fludioxonil.…”
Section: Introductionmentioning
confidence: 97%
“…13,14 The strains resistant to dicarboxamide fungicides contained mutations in the group III histidine kinase gene (HK1), Shk1 in S. sclerotiorum. 13,14 Additionally, histidine kinase gene deletion mutants demonstrated phenotypes of crossresistance to both fungicides. 15,16 The histidine kinase gene is a possible target of dicarboximide and phenylpyrrole fungicides and involved in the high osmolarity glycerol (Hog1) stress response mitogen-activated protein kinase (MAPK) signal transduction pathway.…”
Section: Introductionmentioning
confidence: 99%
“…sclerotiorum. However, repeated use of these fungicides has led to the development of resistance in S. sclerotiorum. In addition, strains that exhibited resistance to dicarboximide fungicides demonstrated resistance to fludioxonil and vice versa. , The strains resistant to dicarboxamide fungicides contained mutations in the group III histidine kinase gene (HK1), Shk1 in S. sclerotiorum. , Additionally, histidine kinase gene deletion mutants demonstrated phenotypes of cross-resistance to both fungicides. , …”
Section: Introductionmentioning
confidence: 99%